Hypertension and Dementia in the Elderly: The Leisure World Cohort Study - Annlia Paganini-Hill (International Journal of Hypertension)
Recent studies have highlighted the deleterious role of cardiovascular risk factors, including hypertension, on the incidence of dementia. Although midlife hypertension is associated with later development of dementia, the role of late-life hypertension remains unclear. We explored the association of hypertension and its treatment with incident dementia in 13978 older (median = 74 years) adults followed from 1981 to 2010 (median = 13 years) and calculated risk estimates using Cox regression analysis in two age groups (<75 and 75+ years) in men and women separately. Dementia status was determined from in-person evaluations, followup questionnaires, hospital data, and death certificates. In the older women, current users of blood pressure medication at baseline had a 26% increased risk of dementia (95% CI 1.06–1.51). In the younger men, those with untreated hypertension and those with past use of blood pressure medication use had about a 30% nonsignificant increased risk of dementia. High blood pressure and its treatment appear to have different effects in men and women and in the old and older.